Influence of Plant Growth Regulators and Medium Strength on Micropropagation of the Biodiesel Plant, Jatropha curcus (Plant Tissue Culture and Biotechnology, 2016)
Leaf explants were cultured to evaluate the effect of different auxins and cytokinins and its concentrations; MS salts on micropropagation of the promising biodiesel Jatropha curcas plant under Egyptian conditions. Results showed that shoot initiated on 0.5 mg/l BA + 0.25 mg/l IBA. Multiplication and elongation were found to be the best using 0.5 mg/l BA in combination with 0.05 mg/l IBA. The multiple shoots were cultured on MS or half strength of MS supplemented with different concentrations of IAA and IBA for rooting phase. Half strength of MS containing 1.0 mg/l IAA was the best for rooting of micropropagated shoots. The rooted plantlets were acclimated in sand : peat?moss mixture (1 : 1) successfully.Plant Tissue Cult. & Biotech. 26(1): 85-96, 2016 (June)